PENGARUH FAKTOR EKSTERNAL DAN INTERNAL TERHADAP IMPULSE BUYING (STUDI KASUS DI ALFAMART CITARUM RAYA SEMARANG) - Kusumawardani, Ovi; Aqmala, Diana (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
Globalization is a process of economic activity and trade, where countries around the world into a single market forces increasingly integrated with the territorial limits of the country without hindrance. Developments in this era of globalization impact to human life. Based on these conditions, affect the appearance of many engaged in the retail trade of daily consumer goods in various cities in Indonesia. This study aims to analyze the effect of Display, Positive Emotion and Store Atmosphere to Impulse Buying.             This study used accidental sampling method on the visitor Alfamart Citarum Raya Semarang. Data obtained by distributing 100 questionnaires to the visitors Alfamart Citarum Raya Semarang. The independent variable in this study is the Display of Positive Emotion and Atmosphere Store while the dependent variable is the Impulse Buying. The statistical methods used in this study is the Multiple Linear Regression Analysis            The results of this study indicate that the variable Display and Positive Emotion there is a significant effect on Impulse Buiyng. As for the Atmosphere Store variables showed no significant effect on Impulse Buying. The results of this study also showed that the value of R Square of 21.6% while the remaining 78.4% is explained by other variables that are not proposed in this study.